Evaluation of PVA Performance with Different Enzyme Concentration - Kamdi, Zakiah; Mohd Zahel, Nurul Syafiqah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The utilisation of high-solubility PVA packing combined with the inclusion of protease enzyme has the potential to be an excellent option for the reduction of bacterial exposure. This study aims to prepare PVA films with varying enzyme concentrations and examine their effects. Mix PVA with 5 enzyme-containing detergent concentrations with ratio 1:0, 1:1, 1:0.5, 1:0.25 and 1:0.125. Fourier transform infrared spectroscopy (FTIR) was used to characterise the PVA film. Immersion tests at different temperatures measured the washing performance. Those PVA/enzyme films take too long to dissolve, so the speed and temperature of the washing test was increased to get the result. In FTIR analysis, the peak seen at wave number 1634 cm-1 represents the carbonyl group. Film with higher ratio of enzyme shows higher ability to remove the stain. High temperature (60oC) needed to dissolve the film.